Metatranslation essays on translation and translation studies - Hermans, Theo 1948- (Routledge, 2023)
"Metatranslation presents a selection of thirteen key essays by leading theorist, Theo Hermans, covering a span of forty years. The essays both trace Hermans' work and demonstrate how translation studies has evolved from the 1980s into the much more diverse and self-reflexive discipline it is today. The book is divided into three main sections: the first section explores the status and central concerns of translation studies, including the growing interest in sociological, ideological and ethical approaches to translation; the second section investigates the key concepts of translation norms and of the translator's presence, or positioning, in translated texts; the historical essays in the final section are concerned with both modern and early modern discourses on translation and with the use of translation as an instrument of war and propaganda. This synthesis of the work of a highly influential pioneer in translation studies is essential reading for researchers, scholars and advanced students of translation studies, intercultural studies and comparative literature"--
Includes bibliographical references and index
Keywords: Translating and interpreting; Essays